ROMANIA'S TOURISM POTENTIAL IN TRANSYLVANIA - Csoka, Gabriela-Elena (Acta Carolus Robertus, 2020)
Tourism becomes a key element of the economy of any country or region that enjoys the existence of tourist resources that can be used. It is a well-known fact and, at the same time, very sad that in Romania, the tourism is under-exploited, although the tourism potential is extremely generous. Therefore, we set out to carry out a consistent study on the consumer behavior in hospitality and tourism demand and offers in Transylvania. Transylvania is one of the oldest and most beautiful historical and folkloric regions of our country. It is located in the center of the country and is the largest region in Romania, including ten counties. In addition to its rich history, Transylvania can boast impressive natural landscapes, but also with many spectacular sights, some of them unique in the country.